Disguise Learn: A Best-in-Class Hybrid Learning Program Case Study - Lapthorne, Alexander (International Journal of Advanced Corporate Learning (iJAC), 2024)
This case study examines the development and implementation of “Disguise Learn”, a hybrid learning program designed to elevate customer training experiences, enhance product adoption, and foster client success in the extended reality (xR) and virtual production (VP) realms. The study highlights the business needs that led to the creation of Disguise Learn, the strategic design of the program, its deployment, change management efforts, and the measurable benefits realised. The study aims to showcase best practices in creating a comprehensive and engaging hybrid learning environment that aligns with organisational objectives and industry demands.